Upaya Meningkatkan Kemampuan dalam Menyusun KTSP melalui Pendampingan Terhadap Kepala Sekolah SD Binaan Kecamatan Paju Epat Kabupaten Barito Timur - Antini, Antini (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to improve teachers' abilities in preparing KTSP through assistance to the principals of SD Fostered Schools, Paju Epat District, East Barito Regency. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of action research that mentoring can improve teachers' abilities in preparing KTSP for the principals of assisted elementary schools in the Paju Epat District, East Barito Regency. Furthermore, the researcher recommends: (1) For school supervisors who have the same difficulties, they can apply assistance to increase the ability to prepare minimum completeness criteria for school principals and assisted teachers. (2) In order to obtain maximum results, individual assistance can be applied intensively and continuously.